GeisteswissenschaftlerInnen: kompetent, kreativ, motiviert - und doch chancenlos? - Solga, Heike; Huschka, Denis; Eilsberger, Patricia; Wagner, Gert G. (Ergebnisse des Expertisenwettbewerbs "Arts and Figures - GeisteswissenschaftlerInnen im Beruf", 2008)
The volume is dedicated to the professional future prospects of graduates of disciplines in the humanities. This group of academics occupies a special position with regard to the rather diffuse professional fields that humanities scholars expect after receiving their degree. Career prospects are less concrete and, in comparison with university graduates from other disciplines, are more subject to fluctuations in demand from the labour market. "All-rounders" or "generalists" are sought, whose competence portfolios must flexibly meet the requirements of future employers.